Perceived Self Efficacy in Implementing COVID-19 Preventive Measures Among Residents of Harari Regional State, Eastern Ethiopia: A Community-Based Cross-Sectional Study - Eyeberu, Addis; Debella, Adera; Mengistu, Dechasa Adare; Arkew, Mesay; Hailu, Saba; Oljira, Amanuel; Yusuf Kebira, Jemal; Getachew, Tamirat; Nigussie, Shamble; Bekele, Deribe; Belete, Rebuma; Abate, Degu; et al. (Frontiers in Epidemiology, 2022)
Abstract Background: The COVID-19 outbreak has now become a major international public health concern and a major challenge for the entire world. Poor adherence to COVID-19 prevention measures continues to be a challenge in managing COVID-19 pandemics, including in Ethiopia. As a result, the current study sought to identify the determinants of community adherence to COVID-19 preventive measures among the adult population of Harari regional state in Eastern Ethiopia. Methods: Community-based cross-sectional study was conducted in Harari Regional State, Eastern Ethiopia from January 05 to 30, 2021. All adults above the age of 18 who lived in Harari Regional State's selected kebeles were eligible to participate in the study. A systematic random sampling method was used to select the study participants. The study included a total of 1320 participants. Pre-tested, structured, and self-administered questionnaires were used to collect data, which was then analyzed using STATA version 16 software. The consent was obtained from each individual and concerned body. Binary logistic regression was used to find the correlation between community adherence to COVID-19 preventive measures and sociodemographic, knowledge, self-efficacy, and risk perception. A P-value of 0.05 was used as the statistical significance cut-off point. Results: One thousand two hundred fifty-five (1255) people took the survey, yielding a 95.1 %. Adherence to COVID-19 preventive measures resulted in a mean cumulative score of 29.8. Six hundred eight (48.5%) of the participants adhered to COVID-19 preventive measures well, while 647 (51.5%) did not. The researchers also discovered a statistically significant link between participants' residence, educational status, income, risk perception, and adherence to COVID-19 preventive measures. Conclusion: Appropriate implementation of COVID-19 preventive measures among community members is required to manage or control pandemics and reduce health-related consequences associated with COVID-19 pandemics. The current study, on the other hand, discovered that nearly half of the study participants had poor adherence. As a result, in order to manage this pandemic, the relevant organizations, including the government and non-governmental organizations, must take appropriate and timely measures. Keywords: community, COVID-19, preventive measures, novel coronavirus, Ethiopia